PENGARUH COMPANY SIZE, RETURN ON ASSET, NET PROFIT MARGIN, FINANCIAL LEVERAGE DAN OPERATING PROFIT MARGIN TERHADAP PRAKTIK INCOME SMOOTHING - Willy Arbiyanto Primatama (Universitas Slamet Riyadi, 2015)
This research purposed to analyze the effect of company size, return on asset, net profit margin, financial leverage and operating profit margin on income smoothing. This research uses purposive sampling method and obtain a sample of 32 manufactured companies listed on The Indonesia Stock Exchange in the year of 2011-2014. The analysis method of this research that used was multiple regressions. The result showed that (1) company size has negative and not significant influence on income smoothing, (2) return on asset has positive and not significant influence on income smoothing, (3) net profit margin has positive and significant influence on income smoothing, (4) financial leverage has positive and not significant influence on income smoothing dan (5) operating profit margin has negative and significant influence on income smoothing.Keywords: company size, return on asset, net profit margin, financial leverage, operating profit margin, income smoothing.